Rethinking the Concept of Team Teaching for English and Non-English Course - Rizkiana Maharddhika (Universitas Insan Budi Utomo, 2019)
Generally, a course is taught by one lecturer during one semester. However, one of the institutions in Malang implemented a team teaching model in almost all courses either English or Non-English course. The courses with two and three credits are strongly advised to implement the team teaching model. In this institution, team teaching model is one subject taught by two lecturers; one lecturer for seven meetings before the middle test, and another different lecturer for seven meetings after the middle test. In other words, students will meet two lecturers for one course in one semester in turn. Hence, in this study, the researcher aims to elaborate the concept of team teaching model implemented in this institution. Then, it compared to the real concept of team teaching implementation from other discussions. As a result, there was a bit misconception in the implementation of team teaching concept in this institution. Overall, this study hopefully contributes the insight of team teaching concept for this institution that could be implemented to all courses properly later on.